Evolution of the UV upturn in cluster galaxies: Abell 1689. Issue 1 (4th May 2018) - Ali, S S; Bremer, M N; Phillipps, S; De Propris, R
ABSTRACT: We have measured the strength of the UV upturn for red sequence galaxies in the Abell 1689 cluster at z = 0.18, reaching to or below the L * level and therefore probing the general evolution of the upturn phenomenon. We find that the range of UV upturn strengths in the population as a whole has not declined over the past 2.2 Gyr. This is consistent with a model where hot horizontal branch (HB) stars, produced by a Helium-enriched population, provide the required UV flux. Based on local counterparts, this interpretation of the result implies Helium abundances of at least 1.5 times the primordial value for this HB population, along with high formation and assembly redshifts for the galaxies and at least a subset of their stellar populations.